Credit risk in microfinance industry: Evidence from sub-Saharan Africa - Sydney Chikalipah (Review of Development Finance, 2018)
Paradoxically, a plethora of empirical evidence in the traditional banking industry claims that smaller loans are associated with higher risk and the exact opposite is true for large loans. In this study we investigate these claims by estimating the relationship between loan sizes and credit risk in the microfinance industry. The sample used for our analysis incorporates over 2000 annual observations, and 632 microfinance institutions drawn from 37 countries of the sub-Saharan African (SSA) region over the period 1995 to 2013. Using the GMM technique, our estimates indicate that credit risk is positively related to loan sizes among microfinance institutions operating in SSA. Our findings have significant implications for the portfolio managers of microfinance institutions operating in SSA, particularly in light of the current wave of mobile money services in many countries.
Keywords: C33; G21; G32; O12; O55; 650; Credit risk; Female borrowers; Loan sizes; Microfinance; sub-Saharan Africa